Analisis Kepatuhan Penggunaan Alat Pelindung Diri Terhadap Covid-19 Pada Petugas Puskesmas Lumpatan - chsan Nur Hamdan; Chairil Zaman; Dewi Suryanti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
COVID-19 has been a major concern all over the world. The assessment of occupational safety and health, as well as infection control and prevention, is required to control and prevent the risk of COVID-19. As a first-level health facility, the public health center plays an important role in dealing with COVID-19. As a result, ensuring that healthcare professionals wear personal protective equipment (PPE) can help to prevent the spread of COVID-19. The purpose of this study is to conduct a compliance analysis of the use of Personal Protective Equipment Against Corona Virus at Lumpatan Health Center in Musi Banyuasin Regency in 2022. This study was conducted between May 28th and June 8th, 2022. A cross-sectional design was used for quantitative research. This study's population consists of healthcare professionals who work at the Lumpatan Health Center. The total sampling method was used to select 46 respondents for the research sample. The results of bivariate analysis using the Chi-Square statistical test show that there is a relationship between education (0.014), knowledge (0.022), attitude (0.012), and supervision (0.002), but no relationship between work length (0.292) and motivation (0.956). The results of a multivariate analysis using multiple logistic regression statistical tests revealed that supervision was the most important factor in PPE compliance (p 0.009 and OR 20,728). It is recommended that healthcare professionals at public health center be more closely monitored in order to increase compliance with the use of PPE.